1986
DOI: 10.2307/2135194
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Sequencing of Marriage and First Birth During Adolescence

Abstract: Whether or not they marry, black adolescent mothers are more likely than whites to attend school following the birth of their first child. Marrying to legitimate a birth reduces the likelihood that a teenager will return to school after childbearing; this impact of marriage is much stronger among black than among white teenagers. The timing of marriage appears to affect school enrollment among white teenagers through its impact on living arrangements. However, the negative impact of marriage on educational ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…16 Furthermore, child marriage is associated with lower educational level attainment. 17 It also is associated with black and American Indian/Alaska Native ethnicities, which suggests a racial/cultural dimension. It is more prevalent in southern parts of the United States, which may reflect local legislation authorizing marriages as early as 14 years of age in Texas and 15 years of age in Mississippi and Georgia, under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, child marriage is associated with lower educational level attainment. 17 It also is associated with black and American Indian/Alaska Native ethnicities, which suggests a racial/cultural dimension. It is more prevalent in southern parts of the United States, which may reflect local legislation authorizing marriages as early as 14 years of age in Texas and 15 years of age in Mississippi and Georgia, under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that once an individual enters a union, he or she runs a higher risk of ending school (Davis and Bumpass, 1976;McLaughlin et al, 1986), and that such effects are stronger for women than for men (Marini, 1978;Alexander and Reilly, 1981;Teachman and Polonko, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…According to some American researchers, the effect of first-birth timing has not been constant across the marriage cohorts. Billy et al (1986), McLaughlin et al (1986) and O'Connell and Rogers (1984) have observed that the effect is somewhat smaller for recent cohorts than it was some year ago. On the other hand, Castro and Bumpass (1987) observed an increasing influence of a premarital birth over the last ten years.…”
Section: Introductionmentioning
confidence: 90%
“…It has been demonstrated that women in the latter subgroup run a higher risk of separation than do those in the former subgroup (e.g., Furstenberg (1979)). Several investigators have used the high degree of marital breakup among those who marry someone other than the biological father as one of the explanations for the divorce level of the total group of women with a premarital birth (e.g., Morgan and Rindfuss (1985), McLaughlin et al (1986), Billy et al (1986)). It is one of the main objectives of our study to split up this heterogenous group, and to see whether those who eventually marry the father of the child also have a much higher divorce rate than do women with a more traditional marriage-birth sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation